2015
DOI: 10.1016/j.actbio.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A novel culture system for modulating single cell geometry in 3D

Abstract: Dedifferentiation of chondrocytes during in vitro expansion remains an unsolved challenge for repairing serious articular cartilage defects. In this study, a novel culture system was developed to modulate single cell geometry in 3D and investigate its effects on the chondrocyte phenotype. The approach uses 2D micropatterns followed by in situ hydrogel formation to constrain single cell shape and spreading. This enables independent control of cell geometry and extracellular matrix. Using collagen I matrix, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…3b-III ), despite their similar morphology. As discussed above, the absence of T low for the patterned PDAC p53 R172H cells is associated with their limited capability of reorganising their cytoskeleton and restricted movement 36 , 37 . The presence of T low in PDAC p53 fl/fl cells shows that individual cells in a cluster were not limited by their neighbouring cells, and maintain similar levels of restructuring activities as the freely moving PDAC p53 R172H cells.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…3b-III ), despite their similar morphology. As discussed above, the absence of T low for the patterned PDAC p53 R172H cells is associated with their limited capability of reorganising their cytoskeleton and restricted movement 36 , 37 . The presence of T low in PDAC p53 fl/fl cells shows that individual cells in a cluster were not limited by their neighbouring cells, and maintain similar levels of restructuring activities as the freely moving PDAC p53 R172H cells.…”
Section: Resultsmentioning
confidence: 88%
“…Therefore, we first evaluated the influence of cell shape on their viscoelastic properties. The micropatterning technique was used as a simple physical means to regulate cell shape as well as restrict cell movement 36 40 . Mutant PDAC p53 R172H cells were cultured on a micropatterned substrate with an array of 20 μm adhesive circles, giving rise to round cell shapes on the patterns (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the aim is the generation of tissue‐ and organ‐like structures for reconstructive purpose, higher complexity levels of biomaterial systems (such as in vitro 3D culture models and in situ biosensing tools) presenting physicochemical and biological cues in a temporospatial manner are absolutely justified . We expect that the future 3D tools and systems will be capable of inducing tissue‐specific cell differentiation, modulating cell geometry and monitoring cellular responses, among others; generate new insights into fundamental cellular behavior information; and lead to more and more biomedical applications ranging from 3D cell culture and production, stem cell therapy, and tissue engineering to drug discovery and development …”
Section: Engineering a 3d Home For Cell Accommodationmentioning
confidence: 99%
“…Histological analysis demonstrated that these scaffolds alone (i.e., cell-free) were able to initiate the formation of well-structured osteochondral tissue. Collagen I gels in combination with 2D micro patterning and single cell culture has also been used as a platform to investigate conditions that control chondrocyte de-differentiation [375]. This approach also offers a method from which niches for targeted differentiation of hMSCs could be investigated.…”
Section: Biomaterialsmentioning
confidence: 99%